Rancang Bangun Pengendali Jarak Jauh Panel Listrik Rumah Berbasis Mikrokontroler Arduino Uno R3 Menggunakan Smartphone Android dengan Komunikasi Bluetooth 3.0 - Bayu Kusumo (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
The home electrical panel is a device that functions to divide electricity from the power source to the loads installed in the house. The operation of the Electrical Panel which is usually done directly by raising and lowering the Mini Circuit Breaker (MCB), then in making this Home Electrical Panel can be operated and controlled remotely without wires (remote). The principle of making this remote controller is the flow of electricity before the MCB is added, switching uses a relay that can be turned on or off by a controller based on the Arduino Uno R3 microcontroller and using an Android smartphone with Bluetooth communication. Programming or coding for Arduino microcontrollers and bluetooth modules using Arduino IDE software and making applications for Android smartphones using MIT App Inventor. Based on the results of the design and testing, by adding switching using a relay with a capacity of 220VAC-10A in each MCB-2A in the four areas of this electrical panel, each area can transmit and disconnect electrical power of 450VA controlled remotely wirelessly (remote) by operating from an Android smartphone with its Bluetooth communication feature with a range of up to 15 meters with obstacles and without obstacles it can still reach 20 meters. The results of this Electric Panel Design have 4 load areas that can be controlled remotely using an Android Smartphone to connect and disconnect electricity from the power source with a recommended maximum capacity of 2A 220VAC or equivalent to 450 VA per area.Keywords: Arduino Uno,Bluetooth, Microcontroller, Relays, smartphones.